MECHANICAL PROPERTIES OF RECYCLED LIGHTWEIGHT CONCRETE MANUFACTURED USING RECYCLED LIGHTWEIGHT CONCRETE AGGREGATE: A REVIEW - Nura Muhammad Ali; Aminu Muhammad (International Journal of Innovations in Engineering Research and Technology, 2022)
In the construction industry, the use of lightweight aggregate is increasing rapidly due to its benefits of; low total dead load, reduction in overall project cost, good insulation properties and how they perform during earthquakes. This offers a solution towards attaining sustainability and low environmental impact in the construction sector. In the production of lightweight concrete, lightweight aggregates typically used are; forming agents that creates stable bubbles within the concrete, pumice, diatomite, perlite, clay, shale and vermiculite. Over the years, researchers have explored the benefits of recycled aggregates like waste tire rubbers and bottom ash on the performance of lightweight concrete. However, research on recycled lightweight concrete aggregate is limited and less detailed. This study reviews the studies conducted using recycled lightweight concrete aggregate and the finding revealed that; despite the satisfactory performance and waste reduction potential, concrete manufactured using recycled Lightweight concrete aggregate displayed lower performance compared to standard concrete. Therefore, more research is necessary towards improving the performance of recycled lightweight aggregate concrete.